A Review on Quantitative Multiplexed Proteomics - Pappireddi, Nishant (Chembiochem, 2019)
Over the last few decades, mass spectrometry-based proteomics has become an increasingly powerful tool that is now able to routinely detect and quantify thousands of proteins. A major advance for global protein quantification was the introduction of isobaric tags, which in a single experiment enable the global quantification of proteins across multiple samples. In this review, we refer to these methods as multiplexed proteomics. We discuss the principles, advantages, and drawbacks of various multiplexed proteomics techniques, and compare them to alternative approaches. We discuss how the emerging combination of multiplexing with targeted proteomics might enable the reliable and high-quality quantification of very low-abundance proteins across multiple conditions. Lastly, we suggest that fusing multiplexed proteomics with data-independent acquisition approaches might enable the comparison of hundreds of different samples without missing values while maintaining the superb measurement precision and accuracy obtainable with isobaric tag quantification.